The modified Gingyo-san, a Chinese herbal medicine, has direct antibacterial effects against respiratory pathogens. Issue 1 (December 2016) - Yamada, Tetsuya; Wajima, Takeaki; Nakaminami, Hidemasa; Kobayashi, Kaho; Ikoshi, Hideaki; Noguchi, Norihisa
Abstract Background Modified Gingyo-san (MGS) is empirically used to treat various respiratory infections. MGS has been reported to have antiinflammatory and antiviral activities; however, it is not known if it has an antibacterial activity. Therefore, in this study, we aimed to investigate the antimicrobial activity of MGS against respiratory pathogens. Methods MGS, which is sold as an over-the-counter drug in Japan, was used for the study. Antimicrobial activity was evaluated using the disk diffusion method. Growth inhibitory activity was evaluated by measuring colony-forming units of the pathogens in the presence of MGS. Results MGS inhibited the growth ofBacillus subtilis, Streptococcus pneumoniae, andStreptococcus pyogenes, which are gram-positive bacteria. Although the growth of most gram-negative bacteria was not inhibited by MGS, interestingly, the growth ofHaemophilus influenzae was inhibited. MGS did not show any activity againstCandida albicans or bacteriophage φX174. Conclusions In addition to the antiinflammatory and antiviral activities of MGS, which have already been reported, the data obtained from this study indicates that MGS has an antibacterial activity.